The rate-determining term of electrocatalytic reactions with first-order kinetics. (10th October 2021) - Huang, Jun; Zhu, Xinwei; Eikerling, Michael
Abstract: The quest to find highly active electrocatalysts for electrochemical energy conversion devices requires mechanistic concepts to guide activity analysis, the most commonly employed ones being the rate-determining step (RDS) and the potential-determining step (PDS). Here we present a generalized concept, the rate-determining term (RDT). The RDT concept is not simply a semantic change but a nontrivial improvement over the RDS and PDS concepts, as it incorporates the detailed kinetics and thermodynamics of multistep electrocatalytic reactions. The theoretical basis of the RDT concept is steady-state microkinetic modelling, for which we put forward a unified and compact formalism for electrocatalytic reactions with first-order kinetics. The new formalism allows us to write the expression for the rate determining term of the reaction in general and analytical form. The RDT concept is then used to derive analytical expressions for the Tafel slope and the volcano plot of activity that can be used in the studies of multistep electrocatalytic reactions. Thereafter, the efficacy of the RDT concept is demonstrated for two important case studies, the oxygen evolution reaction and the carbon dioxide reduction reaction. Fundamental insights into the origins of the potential-dependent Tafel slope are obtained. An important consequence, gleaned from this analysis, is that one cannot infer a RDS from measured Tafel slopes. In addition, kinetic factors are shown to exert a notable influence on the slopes and apex location in volcano plots of activity. The present RDT is anticipated to be a powerful analytical tool for multistep electrocatalytic reactions with first-order kinetics. Graphical abstract: Image, graphical abstract